MODERN ASPECTS OF DIAGNOSIS AND TREATMENT OF ULCER BLEEDING IN PATIENTS WITH LIVER CIRRHOSIS (International Conference on Modern Science and Scientific Studies, 2025)
Upper gastrointestinal bleeding remains one of the most frequent and life-threatening emergencies in gastroenterology and surgery. The greatest difficulty is represented by ulcer bleeding in patients with liver cirrhosis, as it is accompanied by portal hemodynamic disorders, coagulopathy, as well as immune and metabolic dysfunctions.